PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DIREKTORAT JENDERAL PENDIDIKAN ANAK USIA DINI, PENDIDIKAN DASAR, DAN PENDIDIKAN MENENGAH KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET DAN TEKNOLOG - Darmawan, Eric Geovani (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
ABSTRACTThe purpose of this research is to determine the influence of organizational culture and work environment on employee performance. This research uses a survey method with a questionnaire as the instrument. The respondents for this research were 50 employees at the Ministry of Education, Culture, Research and Technology. The sampling process uses a non-probability sampling technique using an associative quantitative approach using primary data. The data analysis technique used is SPSS Version 20.These results show that organizational culture has a positive effect where the value of tcount ttable (2.568 2.011), and is not significant with a value of sig. greater than 0.05 or  0.13 0.05 or 5% of Employee Performance. The work environment has a positive effect where the value of tcount ttable (4.013 2.011) and is significant with a value of 0.000 0.05 or 5% on employee performance. Together, Organizational Culture (X1) and Work Environment (X2) have a positive relationship and from the results of the F test they simultaneously have a significant effect on employee performance with a value of Fcount Ftable (32,966 3.195) with a significant value of 0.000 which is smaller than 0, 05 or 5% of Employee Performance.Keywords: Organizational Culture, Work Environment, Employee Performance